4 - Militaires et militarisme en Afrique: cas du Burkina Faso - Basile Laetare Guissou, (Africa Development, 2023)
There is a tendency to associate military regimes with militarism and civil regimes with democratic ones. This view is supported by the fact that in Africa the most horrible dictatorship have been led by the military. Cases in point are the military regimes led by Idi Amin Dada in Uganda and Bokassa in the Republic of Central Africa. Burkina Faso experienced with the fallacies of military rule as early as independence day when the first Head of State of the state of Upper Volta refused to sign a secret agreement with France on military cooperation. Since then they have played key roles in the successive governments both military and non military. Their involvement in the political management of the country is so deeply engrained in the history and the politics of the society that Burkina Faso is one of the rare African countries where military men or women are allowed to belong to political parties and eventually run for presidential elections.